Intact plasma quantification of the large therapeutic lipopeptide bulevirtide - Sauter, Max; Blank, Antje; Stoll, Felicitas E.; Lutz, Natalie; Haefeli, Walter E.; Burhenne, Jürgen (Analytical and bioanalytical chemistry, 2021)
Bulevirtide is a first-in-class entry inhibitor of the hepatitis B and hepatitis delta virus blocking the sodium/bile acid co-transporter NTCP, and was recently approved for the treatment of hepatitis D as a priority medicine (prime) in an accelerated assessment by the European Medicines Agency. It is a very large lipopeptide comprising 47 amino acids in its sequence and a myristoylation at the N-terminus. For support of clinical development, we established highly sensitive plasma quantification assays using 100 μL of plasma, spanning concentrations of 0.1 to 100 ng/mL and 1 to 1000 ng/mL with the option to measure ten-fold diluted samples up to 10,000 ng/mL. Quantification was performed with UPLC-MS/MS measurements after extraction with protein precipitation. Both assays were fully validated according to the pertinent guidelines of the FDA and EMA, including incurred sample reanalyses and cross-validation using clinical study samples.